Distance between inherent structures and the influence of saddles on approaching the mode coupling transition in a simple glass former - Fabricius, Gabriel (2002)
We analyze through molecular dynamics simulations of a Lennard-Jones (LJ) binary mixture the statistics of the distances between inherent structures sampled at temperatures above the mode coupling transition temperature TMCT. After equilibrating at T>TMCT we take equilibrated configurations and randomly perturb the coordinates of a given number of particles. After that we find the nearby inherent structures (IS) of both the original and perturbed configurations and evaluate the distance between them. This distance presents an inflection point at Tli approximately 1 with a strong decrease below this temperature which goes to a small but nonzero value on approaching TMCT. In the low-temperature region we study the statistics of events which give zero distance, i.e., dominated by minima, and find evidence that the number of saddles decreases exponentially near TMCT. This implies that saddles continue to exist even at T<or=TMCT. As at TMCT the diffusivity goes to zero, our results imply that there are saddles associated with nondiffusive events at T<TMCT.